High-throughput microbial population genomics using the Cortex variation assembler. - Iqbal, Z; Turner, I; Mcvean, G (Oxford University Press, 2013)
SUMMARY: We have developed a software package, Cortex, designed for the analysis of genetic variation by de novo assembly of multiple samples. This allows direct comparison of samples without using a reference genome as intermediate and incorporates discovery and genotyping of single-nucleotide polymorphisms, indels and larger events in a single framework. We introduce pipelines which simplify the analysis of microbial samples and increase discovery power; these also enable the construction of a graph of known sequence and variation in a species, against which new samples can be compared rapidly. We demonstrate the ease-of-use and power by reproducing the results of studies using both long and short reads. AVAILABILITY: http://cortexassembler.sourceforge.net (GPLv3 license). CONTACT: zam@well.ox.ac.uk, mcvean@well.ox.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.